Aplicação da Análise Envoltória de Dados (DEA) para avaliação de desempenho das unidades acadêmicas de uma universidade federal - Melo, Hugo Marciano de (2019)
In a context of political reforms, economic and financial crisis and criticism of the Public Administration, managers and civil servants are expected to respond to the demands of society with greater quality and efficiency. In the context of the Federal Institutions of Higher Education, greater efficiency will be noticed when its teaching, research and extension activities produce the maximum results using the minimum resources available. This research uses the DEA model, with the aid of the Multicri-teria Combinatorial for Scenarios Method for selection of variables, in order to obtain comparative efficiency between academic units of the UFG for the year 2017. As results, it was observed that the UFG operated with technical efficiency of 70.47%, but with an overall efficiency of only 54.84% and that among the 27 Academic Units analyzed, only two are efficient, three have productive inefficiency and the others have inefficiency pure and productive. It concludes that the adoption of the DEA technique in conjunction with other techniques for calculating performance and evaluating results emerges as important mechanisms for identifying failures or pos-sibilities for improvements in the internal dimensions of the institution.